Reference and identity in public discourses - Lutzky, Ursula; Nevala, Minna (Pragmatics & beyond ;, 2019)
"This volume explores the concepts of reference and identity in public discourses. Its contributions study discourse-specific reference and labelling patterns, both from a historical and present-day perspective, and discuss their impact on self- and other-representation in the construction of identity. They combine multiple methodological approaches, including corpus-based quantitative as well as qualitative approaches, and apply them to a range of text types that are or were (intended to be) public, such as letters, newspapers, parliamentary debates, and online communication in the form of reader comments, discussion pages and tweets. In addition to English, the languages studied include Polish as well as European and Latin American Spanish. The volume is aimed at researchers from different research paradigms in linguistics and related disciplines, such as media communication or the social and cultural sciences, who are interested in the interplay of reference and identity"--